LEGAL FORCE OF BINDING SALE PURCHASE AGREEMENT RELATED TO BREACH OF PERFORMANCE AND LEGAL CERTAINTY FOR THE PARTIES (STUDY OF MEDAN DISTRICT COURT DECISION NUMBER 45/PDT.G/2023/PN.MDN) - Juliani Simalango, Yessica; Purba, Hasim; Harianto, Dedi (Penerbit Lafadz Jaya, 2025)
Transfer of land and building rights can be obtained through a legal act of sale and purchase that can be initiated by a PPJB made before a Notary so that the PPJB is essentially an authentic deed that has perfect evidentiary force. However, although the PPJB has often been used by the parties as the basis for the sale and purchase transaction, in practice it still often causes problems because one of them is proven to have committed a breach of contract in the implementation of the PPJB which can be seen in the case in Decision Number 45 / Pdt.G / 2023 / PN.Mdn. The formulation of the problem in this thesis is how is the legal basis for the use of PPJB in regulating the sale and purchase of land and buildings in Indonesia, how is the legal force of PPJB related to the breach of contract carried out by one of the parties in providing legal certainty for the parties, and how is the analysis of the judge's considerations and decisions in civil cases in Decision Number 45 / Pdt. G / 2023 / PN.Mdn. The method used in this research is a juridical-normative research method using primary data and secondary data with interview methods, a statutory regulatory approach, and a case approach, and in drawing conclusions, deductive reasoning is used, namely by thinking fundamentally about general matters and then drawing specific conclusions. The results of this thesis research are that the legal basis for the use of PPJB in regulating the sale and purchase of land and buildings in Indonesia is not contained in the Civil Code but comes from the customary law of Notaries/PPAT based on the principle of freedom of contract, its use is carried out in cases where the signing of the AJB cannot be done before the PPAT, the legal force of the PPJB related to default by one of the parties is if the PPJB is made before a Notary, then the PPJB has strong legal force so that if there is a condition of default because one of the parties does not fulfill its obligations in the PPJB, then the PPJB still has legal force to be implemented, and the considerations and decisions of the Panel of Judges in Decision Number 45/Pdt.G/2023/PN.Mdn which stated that the Defendant was in default in the implementation of the PPJB were appropriate because the considerations were in accordance with the provisions of laws and regulations and the theory of legal certainty so that the PPJB has binding legal force and has provided legal certainty.